2017
DOI: 10.1089/pho.2017.4275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Level Laser Therapy on Bone Regeneration During Osseointegration and Bone Graft

Abstract: A positive effect of low-level laser energy on bone regeneration within a certain relationship between dose and output power was found. LLLT stimulates cellular metabolism, increasing protein synthesis and subsequent bone regeneration. A high dose combined with low power or a low dose combined with high power appears to produce a positive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 34 publications
0
30
0
8
Order By: Relevance
“…20 Studies have shown more evident bone maturation and increased bone-implant contact in LLLT irradiated bone than in control groups. 11,13,16,23 Lopes et al 13 through Raman spectroscopy showed a significant difference in the concentration of calcium hydroxyapatite in irradiated group as compared to control group. Mandic et al, 24 using a split-mouth design, achieved higher stability of irradiated implants than nonirradiated ones in 12 patients.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…20 Studies have shown more evident bone maturation and increased bone-implant contact in LLLT irradiated bone than in control groups. 11,13,16,23 Lopes et al 13 through Raman spectroscopy showed a significant difference in the concentration of calcium hydroxyapatite in irradiated group as compared to control group. Mandic et al, 24 using a split-mouth design, achieved higher stability of irradiated implants than nonirradiated ones in 12 patients.…”
Section: Resultsmentioning
confidence: 97%
“…Statistically significant difference was present between the groups at the end of 6-month (P = .000) and regeneration and speed up dental implant integration in the early healing phases following their placement. 13,16 Studies have agreed that no standard protocol for laser irradiation has yet been defined with reference to implant dentistry. Photobiomodulation has many independent parameters such as wavelength, radiant exposure or energy density (J/cm 2 ), irradiance or power density (mW/cm 2 ), exposure time, and delivery rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser periodontal therapy (LPT) is a laser-based procedure developed as an effective debridement technique to treat periodontitis [130]. Low-level laser therapy (LLLT) with proper doses and output powers was also reported to stimulate cellular metabolism, increase protein synthesis, and subsequently enhance bone regeneration [131]. Temperature could rise in a surgical operation like osteotomies and the elevated temperature could disrupt the bone healing [132].…”
Section: Physical Stimulation For Bone Regeneration and Fracture Healingmentioning
confidence: 99%
“…Na literatura há diversos trabalhos sobre o uso do laser de baixa intensidade com a finalidade de estimular o reparo ósseo em áreas enxertadas RASOULI GHAHROUDI et al, 2014;MARQUEZ MARTINEZ et al, 2008;PINHEIRO et al, 2009;DE OLIVEIRA et al, 2018). Entre os diversos tipos de lasers, o laser com meio ativo GaAlAs vêm sendo avaliado e utilizado com diferentes comprimentos de onda, doses, protocolos de uso e potência de saída (BOSCO et al, 2016;GERBI, 2006;JONASSON et al, 2017;ZEIN et al, 2017) devido ao seu alto poder de penetração nos tecidos quando comparado com os outros tipos de lasers (NISSAN et al, 2006;ÇIRAK et al, 2018;DE OLIVEIRA et al, 2018 O comprimento de onda de 808nm foi utilizado no presente estudo e está dentro da faixa do infravermelho. Também esta dentro da chamada janela óptica a qual abrange os comprimentos de onda do vermelho e próximo ao infravermelho, a luz uma vez obtida nessa faixa, garante a absorção e o espalhamento da mesma fornecendo assim penetração adequada (SELLA et al, 2015; 2018) e proporciona até 54% mais penetração do que a luz com comprimento de onda de 980 nm (HUDSON et al, 2013).…”
Section: Análise Histológicaunclassified